Legume-based green concentrate alleviates negative energy balance and enhances performance, metabolic health, and profitability in postpartum Holstein Friesian cows - Renny Fatmyah Utamy; Ambo Ako; Zyahrul Ramadan; Yasuyuki Ishii; Mohammad Mijanur Rahman; Kannika Umpuch; Azisah Nurfadilah; Gemal Umar Akmal Alkatiry; Muhammad Akram; Jiant Muthahra Maharani (Veterinary World, 2025)
Negative energy balance (NEB) is a common metabolic disorder in postpartum dairy cows that compromises milk yield, metabolic health, and reproductive function. Sustainable nutritional interventions are essential to mitigate NEB without increasing production costs. This study evaluated the effect of a legume-based green concentrate (GC) containing Gliricidia sepium and Indigofera zollingeriana on performance, hormonal profiles, and beta-hydroxybutyrate (BHB) levels in Holstein Friesian (HF) cows experiencing NEB. : Eighteen postpartum HF cows diagnosed with NEB (BHB > 1.5 mmol/L) were randomly assigned to one of three treatment groups (n = 6): Commercial concentrate (CON), GC with 20% legume inclusion (GC20), and GC with 30% legume inclusion (GC30). All cows received concentrate at 3% body weight (dry matter basis) alongside elephant grass for 60 days postpartum. Parameters evaluated included milk yield, feed intake, feed conversion efficiency (FCE), body condition score, daily profit, milk composition, and concentrations of BHB, insulin-like growth factor-1 (IGF-1), estrogen, and prolactin. GC30 significantly improved milk yield (15.88 kg/d), FCE (1.10), and daily profit (United States Dollars 10.99/d), while reducing feed costs and BHB levels in blood (0.91 mmol/L) and milk (0.43 mmol/L) compared to CON (p < 0.05). GC30 also elevated IGF-1 (50.27 ng/mL) and estrogen (104.36 ng/mL), indicating enhanced reproductive readiness. In vitro digestibility and rumen fermentation metrics were also superior in GC-supplemented diets, particularly GC30. No adverse effects were observed on prolactin levels or milk protein and lactose content. Feeding GC, especially GC30, effectively mitigates NEB, enhances productivity, improves hormonal balance, and increases economic returns in postpartum HF cows. This sustainable and cost-effective feeding strategy is suitable for smallholder farmers and supports animal welfare and farm profitability. Future research should explore the effects of long-term GC supplementation and its environmental implications.